A Primer on U.S. “Death” Taxes: An Accurate Description or a Political Perspective? - Hunter, Richard J. (Advances in Social Sciences Research Journal, 2019)
This paper discusses issues relating to estate and inheritance taxes that may be owed to both the federal and state governments as a result of the dearth of a decedent. The paper begins with a brief overview of the requirements of a valid will and outlines the probate process. It then turns to an in-depth discussion of issues relating to estate taxation and strategies that might be utilized to minimize any liabilities and taxes owed either by the estate or by an individual beneficiary.